Assessment of Professed Service Quality of the Cafeteria Business: An Empirical Investigation - Akmal, Syed Mohammad; Hashmi, Abdul Razzak; Mohammad Faisal, Syed; Khan, Ahmad Khalid (International Journal Labs, 2023)
Background: It is important to note that coffee is a phenomenon that has been around for a while in Saudi Arabia. Arabica coffee cultivation on thin basins and bordering mountain slants at elevations ranging from 1200 m to 1800 m in Yemen and Saudi Arabia can be traced back four or five centuries. Aim: The researchers aimed to investigate the factors that have influenced the cafeteria's service quality and compare the effects of the determinants on cafeteria customers in the Saudi Arabian cities of Al Baha and Riyadh. Method: The cafeteria and coffee have been the primary sources of information for the study, which uses SERVQUAL to investigate the causes of perceived facility and eminence in the cafe. An online questionnaire was used to poll a total of 178 respondents. The survey includes 169 respondents who responded most efficiently after applying the pilot study, which let go of irrelevant responses. The analysis through Confirmatory Factor Analysis (CFA) identifies the compelling aspects of the cafeteria in Al Baha and Riyadh, Saudi Arabia, which is ideal for the sector's future strategies. Findings: The study's findings show that three factors significantly impact service quality, performance, convenience, and problem-solving. The other three were unimportant but still hold their importance in this research paper and can be used as sub-independent factors. The culture and habits of Saudi Arabia play a substantial part in the results' anomaly.